IDENTIFICATION AND SOLUTIONS IN DEVELOPMENT OF COMMUNITY-BASED AGROTOURISM: CASE STUDY IN THE TUTUR SUBDISTRICT OF PASURUAN DISTRICT - Syahfirin Abdullah, M. Syamsul Ma'arif Martani Husaini, Tajuddin Bantacut dan Ricky Avenzora (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
ABSTRACT Tourism is becoming advantage commodity, because it’s able to contribute significantly on foreign exchange from non oil and gas commodities. Nowadays, Indonesia is 60th ranking and left behind from other Asian countries. This was caused by some problems of Indonesian tourism. The objectives of this research were to identify and structuralize some problems in agrotourism in Tutur Subdistrict and to obtain the solution for its development. This research was case study using the systemic approach. Data were analyzed by Interpretative Structural Modelling (ISM). The result of this research shows that Tutur Subddistrict agrotourism development have many problems. Main problems were low quality of human resources management and weakness of business orientation. The solution would be to develop training on agrotourism and business to human resources in Tutur subdistrict , so that they can work and manage their business professionally. Keywords: agrotourism, ISM, human resources quality, business , solution, professional